Disaccharidase activity in children with inflammatory bowel disease - Wiecek, Sabina; Wos, Halina; Radziewicz-Winnicki, Igor; Komraus, Marzena; Grzybowska-Chlebowczyk, Urszula (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The etiopathogenesis of inflammatory bowel disease (IBD) is multifactorial and not well explained. Environmental, genetic, and dietary factors play an important role. The aim of the study was the evaluation of lactase, saccharase, and maltase activity in patients with IBD. Materials and Methods: The study comprised 65 children, aged 3-18 years. During a routine endoscopy, we took biopsies from the descending part of the duodenum. In these biopsies, we determined disaccharidase activity using Dahlquist’s method. Results: Decreased lactase activity in the biopsies taken from the small intestine mucosa was most frequently observed in patients with Crohn’s disease (5/15-33%) and least frequently seen in children with lymphocytic colitis (in 1/10-10%). The lowest mean values of lactase activity were found in the children with Crohn’s disease and ulcerative colitis (1.7-2.5 U/1 g). Decreased saccharase activity in the biopsies obtained from the small intestine mucosa was most frequently observed in patients with lymphocytic colitis (in 5/10-50%) and ulcerative colitis (9/20-45%) and least frequently seen in children with non-specific undetermined colitis (in 7/20-35%). Decreased maltase activity in the small bowel mucosa was the most frequently observed in patients with Crohn’s disease (in 5/15-33%) and least frequently seen in children with ulcerative colitis (in 3/20-15%). The lowest mean values of maltase activity were found in the children with Crohn’s disease (5.4 U/1 g). Conclusion: Therefore, it seems reasonable to perform diagnostic examinations aimed at lactose, saccharose, and maltose intolerance and to initiate a dietary regimen in children with IBD.